Effect of Arterial Stiffness and Carotid Intima-Media Thickness Progression on the Risk of Dysglycemia, Insulin Resistance, and Dyslipidemia: a Temporal Causal Longitudinal Study. Issue 3 (March 2022) - Agbaje, Andrew O.; Barker, Alan R.; Mitchell, Gary F.; Tuomainen, Tomi-Pekka
Abstract : Background: We investigated the temporal causal longitudinal associations of carotid-femoral pulse wave velocity (cfPWV), a measure of arterial stiffness, and carotid intima-media thickness (cIMT) progression with the risk of dysglycemia, insulin resistance, and dyslipidemia. Methods: We included 3862, 17.7-year-old, participants from the Avon Longitudinal Study of Parents and Children, followed up for 7 years. cfPWV, cIMT, and fasting plasma samples were repeatedly measured. We computed homeostatic model assessment (HOMA) of insulin resistance and percent pancreatic beta-cell function. Data were analyzed using logistic regression, linear mixed-effect, and cross-lagged structural equation models. Results: A higher cfPWV at 17.7 years was associated with higher insulin at age 24.5 years (odds ratio, 1.25 [CI, 1.08–1.44]; P =0.003), which slightly attenuated after covariates adjustment. Higher cIMT at 17.7 years was associated with lower insulin (odds ratio, 0.06 [0.01–0.95]; P =0.046) at 24.5 years, after covariate adjustments. In mixed-effect models, the 7-year progression in cfPWV (predictor) was directly associated with the increase in triglyceride (outcome). cIMT progression was associated with the 7-year increase in LDL (low-density lipoprotein), triglyceride, and glucose. In cross-lagged models, higher cfPWV at 17.7 years was associated with higher insulin ( β =0.06, SE, 0.12, P =0.014), HOMA of insulin resistance, and HOMA-percent pancreatic beta-cell function at 24.5 years. However, insulin, HOMA of insulin resistance, and HOMA-percent pancreatic beta-cell function at 17.7 years were not associated with cfPWV at 24.5 years. Higher cIMT at 17.7 years was associated with reduced insulin, HOMA of insulin resistance, and HOMA-percent pancreatic beta-cell function at 24.5 years, but not vice versa. Higher glucose at 17.7 years was associated with higher cfPWV and cIMT at 24.5 years only. Conclusions: Arterial stiffness in adolescence may be a causal risk factor for hyperinsulinemia and insulin resistance in young adulthood. Abstract : Supplemental Digital Content is available in the text.